Pengaruh Tenaga Kerja, Modal usaha dan Karakteristik Kewirausahaan Terhadap Keberhasilan UMKM (Studi Kasus Pada Usaha Sektor Makanan dan Minuman) - Ermawati, Ermawati; Rizal, Mohammad; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine and analyze the influence of Labor, Business Capital and Enterpreneurship Characteristics on the Success of MSME in Case Studies in MSME Businesses in the Food and Beverage Sector. The population used in this research is MSME in the Food and Beverage sector in Malang City with a total of 1474 according to the 2023 Central Statistic Agenci Address. The sample taken was 93 respondents using a purposive sampling approach, namely sampling using the Slovin formula. Based on the results of this research, it is known that Labor, Business Capital and Entrepreneurship Characteristics Affect the Success of MSME in the Food and Beverage Sector in Malang City. Laborhas a significan influence on the success variable of MSME in the Food and Beverage Sector in Malang City. Business Capital has a significant influence on the success variable of MSME in Malang City. Keywords: Labor, Business Capitas, Entrepreneurship Characteristics and Succes Of UMKM